Penerapan Strategi Learning By Doing Dalam Meningkatkan Kecakapan Sosial Dan Intelektual Di Racana Wahid Hasyim Semarang - Kholfan Zubair Taqo Sidqi (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2020)
ABSTRACT The Scout Movement is Indonesian National Scout Organization as a non-formal educational institution that organizes scouting education. The Scout Movement functions as an educational organization non-formal outside the school and outside the family and as a forum for fostering and developing students based on the Among System by applying the Scouting Basic Principles and Scouting Methods. Furthermore, the aims and objectives of coaching in the Higher Education Gudep emphasize more on the character development of students and the implementation of Higher Education Tridarma through scouting activities. Not solely for the benefit of the nation and state but scouting in Higher Education there is a concrete phenomenon in the active contribution of, by, and for the future of the Cluster itself. Social development and intellectuals with the "Learning By Doing" strategy also have a mission aimed at making racana members able to realize Higher Education Tridarma (Education, Research, Community Service), and Tri Bina Scout Movement (self-development, Community Development, and Community Development). Intellectual skills enable Racana members to actualize as students, train themselves to think critically, able to take advantage of opportunities for productive life. Whereas social skills Racana members are expected to be able to increase their interaction capacity with other members, be able to solve problems together - continue to develop networking and focus on the work.